Measles outbreak among the Dukpa tribe of Buxa hills in West Bengal, India: Epidemiology and vaccine efficacy - Satinath Bhuniya; Dipankar Maji; Debasis Mandal; Nilanjan Mondal (Wolters Kluwer Medknow Publications, 2013)
Although measles is a vaccine preventable disease, its occurrence and outbreaks are common in India. Four remote and inaccessible hamlets, inhabited by the Dukpa tribe, at Buxa Hills under Kalchini Block of Jalpaiguri District, West Bengal experienced a measles outbreak during the months of April-June, 2011. The authors conducted an investigation to assess vaccine coverage, vaccine efficacy (VE) and to describe the patterns of measles outbreaks in this community. The over-all attack rate was 14.3%; that among males and females were 12.6% and 16.0% respectively (P = 0.189). Attack rate was highest (40%) in 0 to <5 years followed by that in the 5 to <15 years (36.5%). VE was 66.3% (95% of the confidence interval 46.9-78.6%). There is an urgent need to increase the vaccination coverage through special tactics for reaching the unreached.